The Effect of Dietary Chromium on Growth and Survival Rate of Tilapia (Oreochromis niloticus) - Yuliana Yuliana; Subandiyono Subandiyono; Sri Hastuti (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2021)
Tilapia (Oreochromis niloticus) is a freshwater fish commodity in Indonesia. The next problem in aquaculture activities is the low utilization of carbohydrates which causes the role of protein to be reduced. The effort can be done is by adding chromium to feed. Research was conducted on May - July 2019 at Hathcery Fish Center, Siwarak, Central Java. The fish was used for observation have an average weight of 5,97±0,28. The rearing of Tilapia for 42 days using a plastic tub of 1 tail / idensity of 200 fish. The feeding is given twice a day at 08.00 and 16.00 WIB. This trial used an experimental method and a completely randomized design (RAL) with 4 treatments and 5 replications. The treatments were given dose A (2mgCr+3/kg of feed), B (4mgCr+3/kgof feed), C (6mgCr+3/kg of feed) and D (8mgCr+3/kg of feed). Data observed included the level of feed consumption (TKP), feed utilization efficiency (EPP), protein efficiency ratio (PER), protein digestibility, growth rate (RGR) and survival rate. The results showed that chromium had a significant effect (P<0,05) on TKP, EPP, PER, protein digestibility and RGR. Has but no significant effect (P>0,05) on survival. The highgest TKP results in treatment B were 161,66±0,82 g, while the highgest value of EPP PER, protein digestibility, RGR was 34,51±1,25%/day, 1,18±0,04%, 99,89%, 2,15±0,08%. The optimum dose of chromium addition in growth is 3,49 mg/kg. Showed the optimum result during observation.